Bangunan Gereja Inkulturatif Sebagai Sarana Mewujudkan Persekutuan Umat - Abdi Guna Sitepu; Cica Yola Br Sagala (Sekolah Tinggi Teologi Ekumene Jakarta., 2023)
The building of St. Francis of Assisi Berastagi Inculturative Church is inseparable from the meaning of architecture and ornamentation which refers to the Karo traditional house building which is full of meaning. Therefore, through this article, we want to discuss how the meaning of the inculturative church building of St. Francis of Assisi Berastagi and its impact on the development of the Communion of People. The research method used is the qualitative research method. Data collection techniques are carried out through observation, interviews, and documentation. The data obtained will then be analyzed with the Miles and Huberman model through the stages of data reduction, data presentation, and conclusions. The results showed that the inculturative church of St. Francis of Assisi Berastagi symbolizes communion and kinship as the Karo traditional house which is usually inhabited by eight to twelve heads of families. The life of each family of residents of the house is arranged according to the culture and customs that apply to the Karo community. With this church building, the fellowship of people is also getting better. This is evident through the attendance of people in the Eucharist and other very high celebrations in the church. In addition, the fellowship of people is also seen both through activities outside the church both in the station and in the environment.